Remittances, Banking Status and the Usage of Insurance Schemes - Dorothee Crayen; Christa Hainz; Christiane Ströh de Martinez (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Empirical evidence that migrants send home more remittances after disasters raises the question of whether remittances are used to self-insure, substituting for both formal and informal insurance. We investigate this question using a unique dataset on the usage patterns of financial services by households in South Africa. We show that the likelihood that a respondent has a formal funeral cover increases with income and banking status. However, it is lower for individuals receiving remittances, which supports the idea that remittances act as self-insurance. We also show that other risk management strategies influence the purchasing of formal funeral cover. Finally, we find that determinants of informal insurance differ from those of formal insurance.
Keywords: D14; F24; G22; O16; 330; Remittances; insurance; risk management strategies; Versicherung; Konsumentenverhalten; Rücküberweisung (Migranten); Selbstversicherung; Bankgeschäft; Haushaltseinkommen; Lebensversicherung; Schätzung; Südafrika